Hybrid solar array/ac grid power system with near sinusoidal input current - Sheik Fareed Muhammad Musthafa Roomi (2013)
Energy plays a vital role for a country’s national security, economic prosperity and environmental quality. The demand for energy has increased rapidly, especially in developing nations. But the long term reliability of traditional sources of energy remains uncertain, thereby causing limitations of resources. The major concerns are mounting about global climate change those results due to the fossil-fuel combustion which is the major provider of world’s energy. The limitations of resources and the drawbacks in the fuel combustion encouraged the evolution of alternative energy resources.